Rozwiąż równanie
9x-20 do pot.2 -(x-4) do pot.2=8
(4-x)(4+x)+(x-pierw z 2 do opt2)=0
(x- pierw z 3) do pot2- (x- pierw z6) do pot. 2= 2 pierw z 3 -3
(x-5)do pot.2-(3-x)do pot.2= 2 do pot. 6* 4 do pot.4: 8do pot.3
(x+27)(27-x)=9 do pot. 5*81 do pot-1

Wybiorę najlepszą proszę o zapis rozwiązania może być nawet 1 przykład ale żeby był

2

Odpowiedzi

2009-10-20T00:00:01+02:00
(4-x)(4+x)+(x-pierw z 2 do opt2)=0
(4-x)(4+x)+(x-√2²)=0

16+4x-4x-x²+x²-2x*2+2=0
-4x=-18
x=4,5


Najlepsza Odpowiedź!
2009-10-20T01:44:46+02:00
(x-2)²-(x-4)²=8
x²-4x+4-x²+8x-16=8
4x=20 /4
x=5

(4-x)(4+x)+(x-√2)²=0
16-x²+x²-2√2x+2=0
18=2√2x /2√2
x=9√2

(x-√3)²-(x-√6)²= 2√3 -3
x²-2√3x+3-(x²-2√6x+6)=2√3-3
x²-2√3x+3-x²+2√6x-6=2√3-3
2√6x-2√3x=2√3 /:2√3
√24x-√12x=√12
√2*√12x-√12x-√12 /√12
√2x-x=1

(x-5)²-(3-x)²= 2⁶* 4⁴: 8³
x²-10x+25-(9-6x+x²)=2⁶ * (2²)⁴ : (2³)³
x²-10x+25-9+6x-x²=2⁶*2⁸:2⁹
16x=2⁵-16
16x=32-16
16x=16 /:16
x=1

(x+27)(27-x)=9⁵*1/81
27²-x²=9⁵*1/81
(3³)²-x²=9⁵/9²
3⁶-x²=9³
3⁶-3⁶=x²
x² = 0 /√
x = 0